Effect of vrikshayurveda based herbal kunapajala and their doses on mustard productivity: Effect of vrikshayurveda based herbal kunapajala and their doses on mustard productivity - BANAVATH MAHESH NAIK; SUNITA T PANDEY; AMIT BHATNAGAR; SUBASH CHANDRA; RAJEEW KUMAR; NAVNEET PAREEK; KARTHIKA M (Journal of Oilseeds Research, 2023)
The study was conducted during rabi (2020-2021) with Indian mustard at D7 Block of Norman E. Borlaug Crop Research Centre, GBPUAT, Pantnagar. The design used for experimentation was factorial randomized block design (FRBD) with additional treatment. Moreover, crop yields viz., grain yield, stalk and biological yield was resulted significantly more with nettle based herbal kunapajala with higher rate of application. Similarly, control treatment resulted more grain yield, stalk and biological yield as compared to rest treatment. Thus, nettle based herbal kunapajala with higher rate of application performed better seed quality and crop yields.